Are Labor Regulations Driving Computer Usage in India's Retail Stores? - Amin, Mohammad (2012)
A commonly held but untested view is that the use of modern technology such as computers could be endogenous to labor regulations. This paper confirms this view using the Enterprise survey's data on 1948 retail stores in India.